Spectral Signature of the Biosphere: NISTAR Finds It in Our Solar System From the Lagrangian L‐1 Point. Issue 17 (12th September 2019) - Carlson, Barbara; Lacis, Andrew; Colose, Christopher; Marshak, Alexander; Su, Wenying; Lorentz, Steven
Abstract: NISTAR, aboard the DSCOVR spacecraft, is one of the National Aeronautics and Space Administration's energy budget instruments designed to measure the seasonal changes in Earth's total outgoing radiation from a unique vantage point at the Lagrangian L‐1 point a million miles from Earth. Global radiation energy balance measurements are important constraints for climate models, but are difficult measurements to quantify. CERES data offer the best current observational constraints, but need extensive modeling to get global energy. NISTAR observes the entire dayside hemisphere of the Earth as a single pixel, splitting the shortwave radiation into broadband visible and near‐infrared components (analogous to the narrowband spectral ratios used to define vegetation indices). This spectral partitioning at the 0.7‐μm vegetation red edge offers unique constraints on climate model spectral treatment of cloud and surface albedos. Moreover, NISTAR's unique viewing geometry amounts to observing the Earth as an exoplanet, which opens a new perspective on exoplanet observations. Plain Language Summary: NISTAR is an energy budget instrument designed to measure the seasonal changes in Earth' s total outgoing radiation from a unique vantage point aboard the National Aeronautics and Space Administration' s DSCOVR spacecraft orbiting a fixed point a million miles from Earth. From there, NISTAR observes the entire dayside hemisphere as a single pixel. Determining the global energy balance from backscattered radiance measurements is difficult, requiring extensive modeling to fill in the unmeasured angles and unmeasured surface areas in order to convert the measured radiances into radiative fluxes. The daily and seasonal variability in NISTAR data when expressed in the form of spectral ratios provides a unique diagnostic constraint on climate model treatment of cloud and surface albedos. Furthermore, the unique viewing geometry of NISTAR and its broadband spectral partitioning enable robust detection of the biosphere signature of vegetation, thus serving as practical examples of single‐pixel planetary measurements that are directly relevant to exoplanet studies. Key Points: NISTAR makes single‐pixel global energy budget measurements of the Earth' s dayside hemisphere NISTAR data split the reflected solar spectrum into visible and near‐infrared components Spectral ratio time series data provide climate model surface albedo constraints and enable detection of the biosphere spectral signature of Earth